Fracture Resistance of CAD/CAM Lithium Disilicate of Endodontically Treated Mandibular Damaged Molars Based on Different Preparation Designs - Clausson, Carolina; Schroeder, Cristiano Clausson; Goloni, Paulo Vicenti; Farias, Flavio Artur Rego; Passos, Leandro; Zanetti, Raquel Virgínia (International Journal of Biomaterials, 2019)
The aim of this study was to evaluate the fracture resistance of 2 different types of all-ceramic crown using immediate dentin sealing (IDS), obtained using a CAD/CAM system on molars with different preparations. Forty extracted lower molars were endodontically treated and divided into four groups (n = 10) according to the dental preparation. Group 1 (SP0) was prepared without filling the pulp chamber and crown-root junction was located at the cementoenamel junction (CEJ). Group 2 (SP1) was prepared without filling the pulp chamber and crown-root junction was located 1-mm above the CEJ. Groups 3 and 4 contained a flat preparation surface with no axial wall height. Group 3 (CP0) was made IDS with complete filling of the pulp chamber with composite resin and crown-root junction was located at the CEJ. Group 4 (CP1) was prepared with complete filling of the pulp chamber and crown-root junction was located 1-mm above the CEJ. All groups were restored with CAD/CAM lithium disilicate ceramic crowns. Specimens were subjected to the fracture test and statistically analyzed using analysis of variance (ANOVA). Fracture mode was determined using a stereoscopic microscope, classified as repairable or nonrepairable, and analyzed using Fischer’s exact test. Results indicated that there were no significant differences between the groups in terms of fracture resistance or fracture pattern (p >0.05). Fracture resistance was the lowest in the SP0 group, followed by the SP1 group (1634.38 N) of CP0 (1821.50 N), and it was the highest in the CP1 group. There was a predominance of nonrepairable fractures and there were no significant differences in the fracture resistance and fracture mode of CAD/CAM lithium disilicate molar all-ceramic crowns. Endodontically treated molars teeth might be restored with endocrowns or all-ceramic crowns on flat preparation; however tooth fracture failures that affect reliability of these types of restorations should be considered.